For a relational musicology: music and interdisciplinarity, beyond the practice turn - Born, G (Routledge, 2010)
What would contemporary music scholarship look like if it was no longer imprinted with the disciplinary assumptions, boundaries and divisions inherited from the last century? This article proposes that a generative model for future music studies would take the form of a relational musicology. The model is drawn from the author's work; but signs of an incipient relational musicology are found scattered across recent research in musicology, ethnomusicology, and jazz and popular music studies. In support of such a development, the article calls for a reconfiguration of the boundaries between the subdisciplines of music study – notably musicology, ethnomusicology, music sociology and popular music studies – so as to render problematic the music/social opposition and achieve a new interdisciplinary settlement, one that launches the study of music onto new epistemological and ontological terrain. In proposing this direction, the article points to the limits of the vision of interdisciplinarity in music research that is more often articulated, one that – in the guise of a turn to practice or performance – sutures together the historically inclined, humanities model of musicology with the micro-social, musicologically inclined aspects of ethnomusicology. The article suggests, moreover, that this vision obscures other sources of renewal in music scholarship: those deriving from anthropology, social theory and history, and how they infuse the recent work gathered under the rubric of a relational musicology. As an alternative to the practice turn, a future direction is proposed that entails an expanded analytics of the social, cultural, material and temporal in music. The last part of the article takes the comparativist dimension of a relational musicology to four topics: questions of the social, technology, temporality and ontology.